Liquefied gas electrolytes for wide-temperature lithium metal batteries. Issue 7 (26th June 2020) - Yang, Yangyuchen; Yin, Yijie; Davies, Daniel M.; Zhang, Minghao; Mayer, Matthew; Zhang, Yihui; Sablina, Ekaterina S.; Wang, Shen; Lee, Jungwoo Z.; Borodin, Oleg; Rustomji, Cyrus S.; Meng, Y. Shirley
Abstract : Liquefied gas electrolytes with unique solvation structure enable high ionic conductivity in extended temperature ranges, supporting wide-temperature high-voltage lithium metal batteries. Abstract : The momentum in developing next-generation high energy batteries calls for an electrolyte that is compatible with both lithium (Li) metal anodes and high-voltage cathodes, and is also capable of providing high power in a wide temperature range. Here, we present a fluoromethane-based liquefied gas electrolyte with acetonitrile cosolvent and a higher, yet practical, salt concentration. The unique solvation structure observed in molecular dynamics simulations and confirmed experimentally shows not only an improved ionic conductivity of 9.0 mS cm −1 at +20 °C but a high Li transference number ( t Li + = 0.72). Excellent conductivity (>4 mS cm −1 ) was observed from −78 to +75 °C, demonstrating operation above fluoromethane's critical point for the first time. The liquefied gas electrolyte also enables excellent Li metal stability with a high average coulombic efficiency of 99.4% over 200 cycles at the aggressive condition of 3 mA cm −2 and 3 mA h cm −2 . Also, dense Li deposition with an ideal Li–substrate contact is seen in the liquefied gas electrolyte, even at −60 °C. Attributed to superior electrolyte properties and the stable interfaces on both cathode and anode, the performances of both Li metal anode and Li/NMC full cell (up to 4.5 V) are well maintained in a wide-temperature range from −60 to +55 °C. This study provides a pathway for wide-temperature electrolyte design to enable high energy density Li–metal battery operation between −60 to +55 °C.